Large‐scale photovoltaic farms significantly change the vegetation diversity and biomass through influencing soil moisture and physiochemical properties - Shengjuan Yue; Wei Wu; Bo Yuan; Deli Ye; Wenwen Bai (Vadose Zone Journal)
Abstract Large‐scale deployment of photovoltaic (PV) farms alters the surrounding microclimate. Microclimate changes and engineering buildings have caused significant changes in vegetation, although the mechanisms behind change have yet to be thoroughly investigated. The goal of this study was to investigate the vegetation diversity, soil physicochemical properties, and their correlation in large‐scale PV farms in the Qinghai desert area. The results showed that species richness and the Shannon–Wiener index were significantly reduced under the PV panel (p < 0.05), while Simpson and Pielou's index were not significantly different between the PV farm and the control area (p > 0.05). The biomass increased under the PV panel. PV panels increased soil water content while significantly decreasing available phosphorus (p < 0.05). Canonical correspondence analysis showed that available phosphorus content influenced the distribution pattern of plant communities. Redundancy analysis showed that soil water content has a significant impact on plant diversity in Qinghai desert regions. This study has guiding significance for vegetation restoration and management of PV farms in desert areas.